ANALISIS YURIDIS PERANAN WALI NIKAH MENURUT FIQIH ISLAM DAN KOMPILASI HUKUM ISLAM (STUDI PUTUSAN MAHKAMAH AGUNG REPUBLIK INDONESIA NO.261/K/AG/2009) - TAUFIKA HIDAYATI (PREMISE LAW JURNAL, 2013)
ABSTRACT Viewed from the Islamic religion, marriage is one of the methods which are useful to keep people from moral degeneration and destruction. One of the requirements for the validity of a marriage, according to Islam, is wali nikah. A wali nikah is a male who is a Moslem and an akil baligh (adult). Wali nikah comprises wali nasab and wali hakim. The objective of the research was to know and to analyze the role of wali nikah according to Islamic fiqih (the Islamic system of jurisprudence) and the Compilation of the Islamic Law (KHI) in order to know and to analyze the reason of the change from wali hakim to wali nikah of a woman who wanted to get married and to know the legal consideration for a the Judge in making the Ruling No. 261/K/AG/2009 on the Cancellation of Marriage. According to the Islamic Fiqh and KHI, the role of a wali nikah in a marriage contract is a must because he is placed in the requirement in a marriage contract. Keywords: Role of Wali Nikah, Islamic Figh, Compilation of the Islamic Law